Little town on the prairie ebook - Wilder, Laura Ingalls (Little House, 2016)
The seventh book in Laura Ingalls Wilder's treasured Little House series, and the recipient of a Newbery Honor—now available as an ebook! This digital version features Garth Williams's classic illustrations, which appear in vibrant full color on a full-color device and in rich black-and-white on all other devices. The settlement that weathered the long, hard winter of 1880-81 is now a growing town. With spring comes a new job for Laura, town parties, and more time to spend with Almanzo Wilder. Laura also tries to help Pa and Ma save money so that Mary is able to go to a college for the blind. The nine Little House books are inspired by Laura's own childhood and have been cherished by generations of readers as both a unique glimpse into America's frontier history and as heartwarming, unforgettable stories.